Plasma Inflammatory Markers and Ventriculostomy-Related Infection in Patients With Hemorrhagic Stroke: A Retrospective and Descriptive Study - Bögli, Stefan Yu; Wang, Sophie S.; Pietrzko, Elisabeth; Müller, Achim; Eisele, Amanda; Keller, Emanuela; Brandi, Giovanna (Frontiers in Neurology, 2022)
Background. Diagnosis of ventriculostomy-related infection (VRI) remains difficult due to the various existing definitions. In patients with hemorrhagic stroke, its diagnosis might be further complicated by the presence of intraventricular blood. Furthermore, hemorrhagic stroke per se may cause symptoms compatible with VRI. The aim of this study was to evaluate the benefit of plasma inflammatory markers for the diagnosis of VRI and its differentiation from patients with non-cerebral infection and patients without infection in a cohort of patients with hemorrhagic stroke. Methods. 329 patients with hemorrhagic stroke and an external ventricular drain (EVD) in situ were admitted to the Neurocritical Care Unit, University Hospital Zurich over a 6-year period. Of those patients, 187 with subarachnoid hemorrhage and 76 with spontaneous intracerebral hemorrhage were included. Patients with VRI were compared to patients without any infection, and to patients with non-cerebral infection with regards to their clinical characteristics as well as their inflammatory plasma and cerebrospinal fluid (CSF) markers. For the analysis, peak values were considered. Results. VRI was diagnosed in 36% of patients with subarachnoid and 17% of patients with intracerebral hemorrhage. VRI was diagnosed on average day 9±6.2 after EVD insertion, one day after the white blood cell count (WBC) peaked in CSF (8±6.3). Plasma inflammatory markers (WBC, C-reactive protein “CRP” and procalcitonin “PCT”) did not differ among patients with VRI compared to patients without infection. CRP and PCT, however, were higher in patients with non-cerebral infection than in patients with VRI. WBC in CSF was generally higher in patients with VRI compared to both patients without any infection and patients with non-cerebral infection. Conclusions. No differences in plasma inflammatory markers could be found between patients with VRI and patients without any infection. Conversely, CRP/PCT were higher in patients with non-cerebral infection than in patients with VRI. Altogether, CRP, PCT and WBC are not suitable parameters for VRI diagnosis in neurocritical care unit patients.